Contemporary Treatment Practices for Subacute Sclerosing Panencephalitis: A Nationwide Survey Among Adult and Pediatric Neurologists in India - Divyani Garg; Archita Makharia; Ayush Agarwal; Ajay Garg; Achal K Srivastava (Annals of Indian Academy of Neurology)
Background and Objectives: Subacute sclerosing panencephalitis (SSPE) is a progressive disorder caused due to the persistence of mutant measles virus in the brain. Treatment strategies for SSPE remain largely undefined, and there exists no information on how neurologists are currently managing SSPE. Methods: A survey-based study was conducted among Indian neurologists managing pediatric and adult patients with SSPE. A questionnaire-based survey was circulated by email regarding respondent demographics, preference for disease-modifying strategies, and symptomatic therapy. Results: Survey response was obtained from 298 neurologists (responder rate 9.5%) and eventually analyzed from 266 respondents who managed SSPE in routine practice. This included 222 (83.5%) adult and 44 (16.5%) pediatric neurologists from 21 states of India. Ninety-five respondents (35.7%) indicated that they always advised Isoprinosine (inosine pranobex) to their patients. Regarding interferon therapy, 121 (45.5%) reported never advising it, whereas 56 (21.1%) always advised it. For myoclonus, the most frequently used first-line drug was valproate (181, 68%), followed by levetiracetam (58, 21.8%). Most (150, 56.4%) of the respondents favored personalized therapy for the individual patient in terms of the duration of disease-modifying treatment. The patient follow-up was reported to be poor, with most (171, 64.3%) of the patients following up only occasionally and 24 (9%) respondents indicating that patients are lost to follow-up promptly after the initial visit. Conclusions: While SSPE remains a vaccine-preventable illness and the focus should be on prevention through vaccination, there is an unmet urgent need among Indian neurologists for better-defined treatment strategies for patients with SSPE.